Lychee from Florida - A. R. Rafie; Jonathan Crane; Carlos Balerdi; Steven Sargent (EDIS)
HS-1106, a 2-page illustrated fact sheet by A.R. Rafie, Jonathan Crane, Carlos Balerdi, and Steven Sargent, describes this unique fruit originating from southern China, how to pack it for shipment, when it's available, postharvest life, and preparation. Published July 2007.